Pengaruh Penerapan Metode Resitasi Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Terpadu Kelas VII di SMP Negeri 1 Telaga Kabupaten Gorontalo - Debrila Paudi; Sudirman (Jurnal Pendidikan Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of the recitation method implementation on student learning outcomes in social studies subjects for 8th grade at SMP 1 State Junior High School in Telaga, Gorontalo Regency. The study used a quantitative correlational method with a descriptive quantitative approach and obtained the required data from distributing questionnaires to 8th-grade students who learned the social science subject in the said school. As for the sample, 15% of the total population, numbered 40 respondents, were selected with a random sampling technique. Simple linear regression analysis was used as the data analysis method, which was also aided by the SPSS 21 program. The results showed that the recitation method brought upon a positive and significant effect on student learning outcomes, which means that the better the recitation method used, the better student learning outcomes. The coefficient of determination is 74.5%, which means that the variability of student learning outcomes can be explained by the recitation learning method of 74.5%